Diversity, carbon stock and associated biota of seagrass beds in Central Tapanuli District, North Sumatra, Indonesia - MIRA MAULITA; ERICK NUGRAHA; RATNA SUHARTI; NANDA W. TANJUNG; MOHAMMAD SAYUTI; MUGI MULYONO; SAYURI MANTANI; R. HARYO BIMO SETIARTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maulita M, Nugraha E, Suharti R, Tanjung NW, Sayuti M, Mulyono M, Mantani S, Setiarto RHB. 2023. Diversity, carbon stock and associated biota of seagrass beds in Central Tapanuli District, North Sumatra, Indonesia. Biodiversitas 24: 2080-2087. Various human activities emit carbon dioxide which drives global warming and climate change. Seagrass ecosystems can absorb and store enormous quantities of carbon, hence reducing carbon emissions. This research aimed to assess the diversity, vegetation cover, carbon stock and associated biota of seagrass beds in Central Tapanuli District, North Sumatra, Indonesia. Purposive sampling method was employed with data collection used the line transect quadrant method. Carbon stock was measured using the loss of ignition method. There were four species of seagrass in the studied area, namely Enhalus acoroides (L.f.) Royle, Thalassia hemprichii (Ehrenb. ex Solms) Asch., Cymodocea rotundata Asch. & Schweinf. and Halodule uninervis (Forssk.) Boiss. with a density ranging from 23-164 stands/m2. Seagrass cover ranged from 3.87%-34.37%. Associated biota (fish and crustaceans) at each observation station were Siganus javus Linnaeus 1766, Siganus canaliculatus Park 1797, Siganus vermiculatus Valenciennes 1835, Colomesus psittacus Bloch & Schneider 1801, Epinephelus fuscoguttatus Forsskål 1775, Terapon jarbua Forsskål 1775, Ambassis dussumieri Cuvier 1828, Cryptocentrus leptocephalus Bleeker 1876, Leiognathus robustus Sparks & Dunlap 2004, Portunus armatus A.Milne-Edwards 1861, Rhinolambrus pelagicus Rüppell 1830 and Hippolyte obliquimanus Dana 1852. The total carbon stock of the top substrate (leaves) was 12.8 tons, while carbon bottom substrate (rhizomes and roots) was 12.9 tons, resulting in a total carbon stock of 25.7 tons. The analysis of water quality parameters indicated that the studied area had suitable environmental conditions for seagrass growth. The results of this study add new information regarding seagrass ecology of the western region of Indonesia, especially Sumatra.